Mutational landscape of goblet cell carcinoids and adenocarcinoma ex goblet cell carcinoids of the appendix is distinct from typical carcinoids and colorectal adenocarcinomas. (June 2018) - Johncilla, Melanie; Stachler, Matthew; Misdraji, Joseph; Lisovsky, Mikhail; Yozu, Masato; Lindeman, Neal; Lauwers, Gregory; Odze, Robert; Srivastava, Amitabh
Abstract There is limited data on the spectrum of molecular alterations in goblet cell carcinoids and adenocarcinoma ex goblet cell carcinoids of the appendix. We used next generation sequencing to determine mutations of potential pathogenetic and therapeutic significance in this rare group of tumors. Adequate DNA was successfully extracted in 34/46 cases and the final group included 18 goblet cell carcinoids and 16 adenocarcinoma ex goblet cell carcinoids. Illumina TruSeq™ was used for sequencing exons of a custom 282 gene panel using an Illumina HiSeq 2000. All cases had a minimum coverage depth of at least 50 reads. After filtering through the Exome Sequencing Project, the number of mutations per case ranged from 0–9 (mean:3). The mutational burden in adenocarcinoma ex goblet cell carcinoids was significantly higher than goblet cell carcinoids (mean 5 vs. 3;p < 0.05) but the spectrum of alterations overlapped between the two groups. The most frequent mutations includedARID1A (4/34), ARID2 (4/34), CDH1 (4/34), RHPN2 (4/34), andMLL2 (3/34). Some mutations typically seen in conventional colorectal adenocarcinomas were also identified but with much lower frequency (APC :4/34;KRAS :2/34).MLL2 andKRAS mutations were only seen in adenocarcinoma ex goblet cell carcinoids andTP53 mutations were limited to poorly differentiated adenocarcinoma ex goblet cell carcinoids (2/34). Copy number changes could be evaluated in 15/34 cases and showed low copy number gains inCDKN1B (6/15) andNFKBIA (6/15), among others. The overlapping molecular alterations suggest that goblet cell carcinoids and adenocarcinoma ex goblet cell carcinoids are best considered two grades of differentiation of the same tumor rather than two distinct histological types. Mutations inTP53, CDH1 andMLL2 mutations were predominantly present in the adenocarcinoma ex goblet cell carcinoid group consistent with transformation to a higher grade lesion. The unique mutational profile also offers an explanation for the poor chemosensitivity in these tumors and highlights the need for developing new targeted therapies.